Motivation of software engineers and its factors - Sharma, Sagar; Stříteský, Marek; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The main goal of this thesis is to investigate the vital realm of employee motivation with the purpose of obtaining an in-depth understanding of the employee motivation of software engineers and explore the factors influencing this motivation, at various international companies in Prague. Furthermore, as part of secondary goals, qualitative data through interviews was collected in order to understand how employee performance and job satisfaction are related to motivation of software engineers. To answer the proposed research questions, qualitative research was conducted in the form of interviewing 15 software engineers. The qualitative data collected was then analyzed and divided into three main categories; ‘Motivation of software engineers’, ‘Influence of intrinsic and extrinsic motivation on employee performance’ and ‘Job satisfaction and motivation’.
Vedoucí práce: Marek Stříteský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses